Analysis of the Influence of Brand Image, Promotion Effectiveness, and Price on Customer Loyalty at Cassandra Skincare Singkawang - Anike Cariati Mahanani; Ananda Archie (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of brand image, promotion, and price on customer loyalty at Cassandra Skincare Singkawang. The background of this research is driven by the intense competition in the beauty industry and the income fluctuations experienced by Cassandra Skincare over the past three years. This research uses a quantitative method with an associative approach. The research sample consisted of 100 respondents determined through purposive sampling with the criterion of consumers who have undergone treatment at least twice. Data were collected through questionnaires and processed using SPSS version 22. The results of the study show that brand image, promotion, and price have a positive and significant influence simultaneously on customer loyalty. The t-test results show that brand image, promotion, and price have a positive and significant influence partially on customer loyalty. The coefficient of determination (R²) of 59.2% indicates that these three variables can explain customer loyalty well, while the remaining percentage is influenced by other factors outside this research model. This research is expected to provide practical benefits for Cassandra Skincare in formulating marketing strategies to maintain customer loyalty. As a suggestion, the company should continue to maintain service quality, strengthen brand image, and offer attractive promotional programs and competitive pricing. Recommendations for future research are to add other variables such as service quality, consumer trust, or customer satisfaction so that the analysis results are more comprehensive. In addition, the research coverage area can also be expanded to obtain more representative findings.